The Prevalence of Thyroid Disorders in Patients With Vitiligo: A Systematic Review and Meta-Analysis - Yuan, Jinping; Sun, Chong; Jiang, Shibin; Lu, Yansong; Zhang, Yuhui; Gao, Xing-Hua; Wu, Yan; Chen, Hong-Duo (Frontiers in Endocrinology, 2019)
Background: Associations between vitiligo and thyroid disorders have been suggested, However, the prevalence of thyroid disorders in vitiligo vary widely. Purpose: To conduct a systematic review and meta-analysis assessing the prevalence of thyroid disorders in patients with vitiligo. Method: The PubMed, Cochrane Library, EMBASE, CNKI (China National Knowledge Infrastructure), Chongqing VIP database and Wanfang database from inception to August 2, 2018 were systematically searched. The pooled prevalence and its 95% confidence interval (CI) were calculated. Results: A total of 77 eligible studies were identified and included, published from 1968 to 2018. Six thyroid disorders including subclinical hyperthyroidism, overt hyperthyroidism, subclinical hypothyroidism, overt hypothyroidism, Graves disease, and Hashimoto thyroiditis were described. The numbers of relative studies were 54 in overt hypothyroidism, 50 in overt hyperthyroidism, 25 in subclinical hypothyroidism, 19 in Hashimoto thyroiditis, 16 in Graves disease, and 10 in subclinical hyperthyroidism. The highest prevalence was 0.06 (95% CI: 0.04-0.07) in subclinical hypothyroidism, and the lowest was 0.01 in subclinical hyperthyroidism (95% CI: 0.00-0.01) or Graves disease (95% CI: 0.01-0.02). Conclusion: Six thyroid disorders showed various prevalence in vitiligo. The highest prevalence was in subclinical hypothyroidism, and the lowest was in subclinical hyperthyroidism or Graves disease. Screening vitiligo patients for thyroid disorders seem plausible, in an effort to detect potential thyroid diseases or to assess the risk of future onset.